The Effects of Integrity Campaign Towards Managing Ethical Change During National Examinationi - Nia Sarinastiti (Atma Jaya Indonesia Catholic University, Jakarta, 2017)
The objective of this research is to review the effects of an integrity campaign during the national examination for elementary until high school students. For two years, 2015 and 2016, the Ministry of Education and Culture conducted a campaign that focused on an effort to decrease cheating during examinations by placing the responsibility to each of the municipal/regency throughout Indonesia. The theme “Prestasi penting, jujur yang utama” or in short “Prestige is important, but honesty is first” received many responses, including government officials who are shocked on the results of their schools. The theoretical approach is using Smith’s evaluation of awareness, acceptance and action objectives to help understand government communication efforts in changing the mindset and behavior of its stakeholders. The research method focuses on qualitative data, which are anecdotes (through interviews and documents) and observations, supported by response data managed by the Ministry of Education and Culture for 2015 and 2016 campaigns. The findings of the research indicated that all hierarchy of objectives were reached; and therefore, the campaign was effective